The New Clustering Algorithm with Cluster Members bounds for energy dissipation avoidance in wireless sensor network - Babaie, S; Zadeh, A K; Amiri, M G (2010 International Conference On Computer Design and Applications, 2010)
Energy consuming limitation often is main problem in wireless sensor networks. In this paper we introduce a new algorithm for reduce energy consumption and Increase the useful lifetime of wireless sensor networks with cluster member bounds. This paper introduces the new energy adaptive protocol to reduce overall power consumption, maximize the network lifetime in a heterogeneous wireless sensor network. In our protocol, NCACM (the New Clustering Algorithm with Cluster Members bounds for energy dissipation avoidance in wireless sensor network), determine a confidence value for any node that want be a cluster head with parameters such as nodes remaining energy and distance between nodes and distance between cluster heads in each round then clustering provide. Simulation results show new algorithm has better performance as LEACH and LEACH-E and cause to reduce energy consumption and progress wireless sensor network performance and lifetime.